Perbandingan skor SOFA pada pasien sepsis dengan dan tanpa diabetes melitus tipe 2 - Nares Wari, Munsyi; Fadrian; Yerizel , Eti; Reza , Mohamad; Aprilia , Dinda; Nofita , Eka (Faculty of Medicine, Universitas Andalas, 2026)
Comparison of SOFA scores in septic patients with and without type 2 diabetes mellitus Sepsis is a life-threatening organ dysfunction. A dysregulated host response to infection causes it. Organ dysfunction can be represented by an increase in the SOFA score of > 2 points. Every increase in the score reflects worsening of organ dysfunction. Type-2 Diabetes Mellitus (T2DM) is one of the most common comorbidities in sepsis patients. T2DM patients have chronic hyperglycemia. This condition can impair immune function and damage the endothelium. Objective: To find out the comparison of SOFA scores in sepsis patients with and without T2DM. Methods: This research was an analytical, cross-sectional study using medical record data from RSUP Dr. M. Djamil Padang. The 132 samples comprised 66 sepsis patients with T2DM and 66 without T2DM. Sampling was carried out by using a stratified random sampling technique. Bivariate data analysis used an independent-samples t-tes. The mean of SOFA scores in sepsis patients with T2DM was 8.05 +_ 2.36 and the mean of SOFA scores in sepsis patients 6.38 +_ 2.96. The p-value (<0,05) in both groups was 0.001. Conclusion: There is a significant difference in SOFA scores between sepsis patients with and without T2DM. Keywords: sepsis, SOFA score, T2DM